CORRELATION BETWEEN LEVEL OF SERUM FETUIN-A AND BLOOD VESSEL CALCIFICATION IN PATIENT UNDERGOING REGULAR HEMODIALYSIS - Daniel Reinaldo. P. Situmorang, Riri A. Muzasti, Syafrizal Nasution1, NettyLubis (International Journal of Research Science and Management, 2019)
Introduction: Cardiovascular disease is one of the main causes of death in patients with chronic kidney disease (CKD) undergoing hemodialysis or peritoneal dialysis therapy. This is related to calcification in large blood vessels such as the aorta. Fetuin-A is a protein that could prevent calcification process happening in blood vessel wall. Method: This study is a cross-sectional analytic study with research subjects is the patient of chronic kidney disease undergoing regular hemodialysis in the hemodialysis unit of RSKG RASYIDA Medan starting from April 2018 (for at least ≥ 3 months) and aged≥ 18 years. Fetuin-A level test and abdominal x-ray were conducted, then statistical analysis performed to know the correlation of serum fetuin-a level with calcification of blood vessels in regular hemodialysis patients. Result:Of the 113 research subjects, those who did not have calcifications had higher Fetuin-A levels than mild and severe degrees of calcification (417.02 ± 228.87 mg / dl, 353.57 ± 172.95 mg / dl, 267.04 ± 127 , 52 mg / dl, respectively). Conclusion: Serum fetuin-A levels were associated with the occurrence of blood vessel calcification in regular hemodialysis patients (p = 0.004).